EMPIRICAL INVESTIGATION IN CEOCOMPENSATION ACROSS CONTINENTAL EUROPE AND UNITED KINGDOM - Baužytė, Inga (Ekonomika, 2010)
The article presents a detailed investigation of the top management / Chief Executive Officer (CEO) remuneration package and reveals why this is important to the economy. The goal of this paper is to examine the CEO pay (salary + bonus), wealth delta, cumulative value of options held and total compensation throughout Continental Europe and the United Kingdom across a number of various sectors during years 2005 and 2006. Attention is turned to the pre-crisis data analysis which might instigate the argument that CEO compensation was one of the main reasons which lead management to the excess risk taking and reckless decision making. Therefore, it might be concluded that the relationship between risk and executive remuneration can be more subtle and complex than it has been thought. The paper applies the multiple regression model supported by research hypothesis postulation tested by the correlation method and T-test approach.